Kebijakan Manajemen Bencana dan Peran Teknologi dalam Mitigasi Resiko - Maulidah, Hillyah; Saepudin, Eli Apud; Azzahra, Shabna; Afrilian, Alita Harya; Ramadani, Ipat; Qurrota A’yun, Nova (UNIVERSITAS SERAMBI MEKKAH, 2025)
Disaster management in Indonesia, particularly in risk mitigation. Through case studies in several disaster-prone areas, it identifies gaps and challenges in policy implementation. Although there are various relevant policies, inter-agency coordination, community involvement, and limited budget allocations are the main obstacles. There is a need to improve inter-agency coordination, community capacity building, and more adequate budget allocation to increase the effectiveness of disaster mitigation.The development of information technology has opened new opportunities in disaster mitigation, the role of technology in improving the effectiveness of disaster mitigation in Indonesia. In some areas that have adopted disaster mitigation technology, it has been shown that technology can increase speed in early detection of disasters, accuracy in impact estimates, and efficiency in communication and coordination. However, obstacles such as limited access to technology in remote areas and lack of competent human resources are challenges that need to be overcome.Synergy between disaster management policies and technology utilization in reducing disaster risk. Several regions in Indonesia have shown that a combination of comprehensive policies and appropriate technology utilization can increase community resilience in the face of disasters. This paper suggests the need to develop an integrated early warning system, utilize spatial data for risk analysis, and increase the capacity of the community in using technology.